Nerve Complications after Regional Anesthesia in Foot and Ankle Surgery Avoiding the Popliteal Fossa. Issue 2 (April 2022) - Bartholomew, Ania; Ciesa, Michael; Slone, Tyler; Cheney, Nicholas A.; Clark, Brian C.
Category: Ankle; Arthroscopy; Hindfoot; Lesser Toes; Midfoot/Forefoot; Other Introduction/Purpose: Popliteal nerve blocks are a common procedure employed by anesthesiologists to augment intraoperative anesthesia as well as provide postoperative pain control. Unfortunately, these can be associated with unintended complications. These complications may be sensory or motor including pain, numbness, and foot drop, sometimes without clear resolution. Studies suggest complications higher than previously reported, Lauf (2020). Our study looked to address the complication rates from an alternative anesthetic procedure, a distal ankle nerve block which involves anesthesia to the five nerve(s) more intimately involved in the surgical procedure. This alternative technique may provide equivalent anesthetic properties and pain relief as the popliteal blocks, with less motor and sensory complications for many patients across various demographics. Methods: We retrospectively reviewed patient charts and messaging from 2019 to 2021 that received a distal ankle field block for various surgical procedures including ankle arthroscopy, ankle fractures, and lateral ankle stabilizations. The five nerves anesthetized in the distal ankle nerve block included the tibial, superficial and deep peroneal, sural, and saphenous. Thus far, 90 surgeries have been reviewed and analyzed for neuropathic complications and confirmed via EMG. Results: Of the 90 patients analyzed, 3 patients were found to have a superficial peroneal neuropathy that included dorsal numbness as a result of the distal ankle block, resulting in a 3.33% complication rate. 1 patient required a rescue block to be performed post-operatively for pain. The remaining 87 patients recovered appropriately and without complications. No motor complications have been found from patients receiving distal ankle nerve blocks, as performed by the senior author. Conclusion: With the absence of motor complications and markedly reduced incidence of sensory complications, distal ankle nerve blocks may be a beneficial alternative to popliteal nerve blocks for various foot and ankle orthopedic surgeries. As motor complications can result in life altering disability, an anesthetic procedure with reduced negative motor outcomes can improve surgery and recovery prognosis. Future directions for this study include adding more patients to increase the sample size, as well as continuing to follow current patients, monitoring symptoms or complications.